ANALISIS KEBIJAKAN PEMBERIAN KREDIT DAN PENGARUH NON PERFORMING LOAN TERHADAP LOAN TO DEPOSIT RATIO PADA PT. BANK RAKYAT INDONESIA (PERSERO), TBK CABANG RANTAU, ACEH TAMIANG. ( PERIODE 2007-2011) - Nurul Fitria; Raina Linda Sari (Departemen Ekonomi Pembangunan USU, 2012)
Formulation of the problem in this research is How lending policy applied to PT Bank Rakyat Indonesia (Persero) Overseas Branch, Aceh Tamiang and the influence of non-performing loans (NPL) to loan to deposit ratio (LDR). The purpose of this study was to determine the credit policies were applied, and also find out if non-performing loans significantly affect the loan-to-deposit ratio. The hypothesis in this study is suspected of lending policies that are both based on the theories of credit policy with the principles 5C, and the significant influence of the non-performing loans to the loan-to-deposit ratio. The collection of secondary data obtained through company documents and other reports relevant to this study include: financial statement data for the five years from 2007 to 2011, books, company literature, and other data related with the object of research. The analysis method used is descriptive analysis is used to analyze the credit policy on the first hypothesis and simple regression analysis for the second hypothesis. In the first hypothesis of the study results show that the principle of prudence in lending policy is the principle 5C consisting of: Character, Capacity, Capital, Collateral, Condition. In the second hypothesis test simple regression analysis showed a significant effect of the non-performing loans to the loan-to-deposit ratio.